Learning Across A Lifetime of Learning: Stages of Teacher Development - Charles Kent Runyan; Steve Brown; Carolyn Fehrenbach; Kenny McDougle; Pam Sells; Ray Willard (The Advocate, 2014)
This study presents a conceptual framework for examining the developmental stages of teachers and illustrates the differences found in student teachers as they develop. The research illustrates how by assessing a teacher candidate’s own perception of importance, mastery, and desire to improve, an instrument can be used to prioritize needs at different points of a teacher’s career as well as identify stages of development. The statistical data, analysis, and interpretation of a study utilizing the Teacher Need Assessment Questionnaire (TNAQ) with teacher candidates is displayed.